Utaut Effects On Online Food Ordering Platform Use And Culinary Sme Performance In Medan - Ayu Annisa Fikra; Muhammad Irwan Padli Nasution; Rahmi Syahriza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the influence of the Unified Theory of Acceptance and Use of Technology (UTAUT) model on the use of the GoFood online food ordering platform and its impact on the performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Medan City. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The study sample consisted of 210 culinary MSME operators in Medan City, selected using probability sampling. Primary data were collected through the distribution of structured questionnaires and analyzed using SmartPLS 3 software. The results indicate that Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions have a positive and significant effect on Behavioral Intention. Furthermore, Behavioral Intention and Facilitating Conditions have a positive and significant effect on Use Behavior, while Use Behavior has a positive and significant effect on SME performance. In addition, Facilitating Conditions also have a direct positive effect on SME performance. These findings indicate that the successful adoption of the GoFood platform by culinary MSMEs is influenced not only by perceived benefits, ease of use, and social influence but also by the availability of technological infrastructure and adequate facility support, which can enhance business performance. This study provides empirical evidence regarding the relevance of the UTAUT model in explaining the adoption of digital technology among culinary MSMEs amid the digital transformation.